Pressure‐Suppressed Carrier Trapping Leads to Enhanced Emission in Two‐Dimensional Perovskite (HA)2(GA)Pb2I7. Issue 40 (13th August 2020) - Guo, Songhao; Zhao, Yongsheng; Bu, Kejun; Fu, Yongping; Luo, Hui; Chen, Mengting; Hautzinger, Matthew P.; Wang, Yingqi; Jin, Song; Yang, Wenge; Lü, Xujie
Abstract: A remarkable PL enhancement by 12 fold is achieved using pressure to modulate the structure of a recently developed 2D perovskite (HA)2 (GA)Pb2 I7 (HA= n ‐hexylammonium, GA=guanidinium). This structure features a previously unattainable, extremely large cage. In situ structural, spectroscopic, and theoretical analyses reveal that lattice compression under a mild pressure within 1.6 GPa considerably suppresses the carrier trapping, leading to significantly enhanced emission. Further pressurization induces a non‐luminescent amorphous yellow phase, which is retained and exhibits a continuously increasing band gap during decompression. When the pressure is released to 1.5 GPa, emission can be triggered by above‐band gap laser irradiation, accompanied by a color change from yellow to orange. The obtained orange phase could be retained at ambient conditions and exhibits two‐fold higher PL emission compared with the pristine (HA)2 (GA)Pb2 I7 . Abstract : A remarkably enhanced emission (by 12‐fold) is achieved using pressure to modulate the structure of a highly distorted 2D halide perovskite (HA)2 (GA)Pb2 I7 . In situ structural, spectroscopic, and theoretical analyses reveal that lattice compression under a mild pressure within 1.6 GPa considerably suppresses the carrier trapping, leading to the significantly improved performance.